From Frontier to Midlands : a history of the Graaff-Reinet district, 1786-1910 - Smith, Kenneth Wyndham (Rhodes University, Faculty of Humanities, Department of History, 1975)
The study of local history in South Africa is still in its infancy and has not been accorded the same recognition as elsewhere. There is no convenient manual to guide the would-be local historian of the Cape. There are few models that provide an insight into the main problems encountered by the local historian of a Cape community. In such local histories as exist, attention has been focussed predominantly on the foundation and physical growth of towns, the naming of streets, the establishment of schools and hospitals. Many of these accounts were written for publicity purposes or to commemorate the founding of towns. Although there is no history of the Dutch Reformed Church in Graaff-Reinet, the history of local congregations of the Dutch Reformed Church has generally been well covered in the form of Gedenkboeke and other studies. These frequently have a particular relevance as many towns such as Burgersdorp and Colesberg were founded as a result of the initiative of the church. Preface.
Keywords: Graaff-Reinet (South Africa) -- History; South Africa -- Economic conditions -- History; South Africa -- Politics and government -- History; Frontier and pioneer life -- Graaff-Reinet